Book review. Issue 2 (5th June 2015) - Shaver, Michael P.
Abstract : A review of 'Handbook of Green Materials: Processing Technologies, Properties and Applications' by Kristiina Oksman, Aji P Mathew, Alexander Bismarck, Orlando Rojas and Mohini Sain (eds). World Scientific, 2014, 1124pp. ISBN: 978-981-4566-45-2 (Hardback: £1043). ISBN: 978-981-4566-47-6 (ebook: £782).